STRATEGI PENCAPAIAN KOMPETENSI DASAR PADA ERA Ã¢â‚¬Å“NEW NORMALÃ¢â‚¬Â DI SD NEGERI INPRES KOYA TENGAH DISTRIK MUARA TAMI KOTA JAYAPURA - Aisyah Ali; Sukmawati Sukmawati (LPPM Uncen, 2023)
This community service activity was carried out at Inpres Koya Tengah State Elementary School, Muara Tami District, Jayapura City with the aim of assisting teachers in determining strategies for achieving minimum competencies in the New Normal era at Inpres Koya Tengah State Elementary School, Muara Tami District, Jayapura City. The target audience for this activity are school principals, teachers, both class teachers and subject teachers at SD Negeri Inpres Koya Tengah, Muara Tami District, Jayapura City, including honorary teachers. The method we use in carrying out this activity is the lecture and mentoring method with systematically designed stages consisting of preparation, activity implementation and evaluation stages. This activity went well and gave positive results to the implementation of learning at SD Negeri Inpres Koya Tengah, Muara Tami District, Jayapura City, Papua.Ã‚Â Keywords: Strategi; Minimum Competency; New normal